2020
DOI: 10.1590/1980-5373-mr-2019-0463
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Immobilized on Fibrous Clay as Strategies to Photocatalytic Activity

Abstract: TiO 2 immobilized in Sepiolite (TiO 2 /Sep) was successfully prepared by the sol-gel technique, with titanium isopropoxide as the precursor for the formation of TiO 2 in the anatase phase calcined at 400 °C. The prepared samples were characterized by X-ray diffraction, Fourier Transform Infrared spectroscopy, Scanning Electron Microscopy coupled to energy dispersive spectroscopy, and thermogravimetric analysis. The results showed that TiO 2 /Sep structure was identified in all characterizations, showing the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 59 publications
(87 reference statements)
4
27
0
Order By: Relevance
“…The photocatalyst promoted a higher number of active sites, consequently increasing the concentrations of hydroxyl radicals and superoxides [ 55 ]. However, the radicals can recombine and inhibit the photocatalytic process, and a large amount of suspended material can cause the inhibition of light passage, implying a decrease in the photocatalytic efficiency [ 56 ]. Similar behavior was reported by Wang et al [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocatalyst promoted a higher number of active sites, consequently increasing the concentrations of hydroxyl radicals and superoxides [ 55 ]. However, the radicals can recombine and inhibit the photocatalytic process, and a large amount of suspended material can cause the inhibition of light passage, implying a decrease in the photocatalytic efficiency [ 56 ]. Similar behavior was reported by Wang et al [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…The degradation rate increased with the increase in the number of protons, following the order pH 10 (22%), pH 7 (41%), and pH 3 (47%); therefore, it increased by about 25% compared to the alkaline medium. The low degradation at pH 10 can be attributed to competition between the surface charges of the photocatalyst, which are slightly altered and may be protonated/deprotonated, consuming the hydroxyl radical and consequently decreasing the degradation rate [ 56 , 60 ]. Wang et al [ 9 ] observed that the degradation of IBU was directly affected by the pH of the solution, with the highest degradation rate (49.45%) in acidic pH values.…”
Section: Resultsmentioning
confidence: 99%
“…2, there are an array of 8 main peaks that appeared in FTIR spectrum of TiO 2 -caly nanocomposite sample. the presence three stretching bands between 3800 and 3600 cm -1 are likely assigned to OH groups of absorbed water molecules as well as water coordinated to magnesium or surface of clay structure 32 . The fairly wide peak appread at 3419 cm -1 is attributed to O-H stretching vibration, representing hydroxyl groups of glucose and starch hydrocarbons 33 .…”
Section: Ftir Analysismentioning
confidence: 99%
“…The peak at 1641 cm -1 likely re ects the presence bending vibration of OH group of water molecules in interlayer of TiO 2 -caly nanostructured. The vibration of Si-O-Si bonds at ngerprint region of1036 and 1461 cm -1 perhaps are representative of sheet-like silicates in clay mineral 32 . Finally, Ti-O bonding of anatase type was appeared at 528 cm -1 and 440 cm -1 bands indicating immobilization of the titania NPs on clay structure 35,36 .…”
Section: Ftir Analysismentioning
confidence: 99%
“…Highly crystallized and high porosity anatase samples allow the access of large organic molecules as well as light during the reaction [ 120 ]. pH can influence differently the degradation of contaminants [ 38 , 156 ] because, in acidic or alkaline conditions, the TiO 2 surface can be protonated or deprotonated [ 156 , 157 ].…”
Section: Photocatalysis With Supported Materialsmentioning
confidence: 99%